THE TEMPORALITY OF LONGING: WAITING, SILENCE, AND EMOTIONAL TIME IN SARAT CHANDRA CHATTOPADHYAY’S PARINEETA - Supriya (International Journal of Research -GRANTHAALAYAH, 2026)
Sarat Chandra Chattopadhyay occupies a singular, almost peerless position in the canon of Indian literature as the quintessential chronicler of the "private life.". Where the Jewish geniuses of his time, with whom, or even with the greatest of them, the Great Nationalist Project was underway, or the moral awakening of the Indian soul, Sarat Chandra retreated, to the microscopical pang of the English fireside (Basnet et al., 2011). The epochal political movements in the colonial Calcutta or even the changes of the British Raj do not consider the time in his 1914 novella Parineeta. Rather it is estimated by the movements of the grandfather clock in the fancy hallway Nabin Roy; the charmless and inexpressive measures of the beating of the heart of Lalita.